2014
DOI: 10.1016/j.clinph.2013.12.102
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in startle-evoked arm movements increase with impairment following stroke

Abstract: Objective The startle reflex elicits involuntary release of planned movements (startReact). Following stroke, startReact flexion movements are intact but startReact extension movements are impaired by task-inappropriate flexor activity impeding arm extension. Our objective was to quantify deficits in startReact elbow extension movements, particularly how these deficits are influenced by impairment. Methods Data were collected in 8 stroke survivors performing elbow extension following two non-startling acoust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 58 publications
4
25
1
Order By: Relevance
“…Previous reports at the elbow showed inappropriate flexor activity that lead to deviations away from stroke subject's intended target (Honeycutt and Perreault, 2012, Honeycutt and Perreault, 2013); however we did not find evidence of this in the hand indicated by a strong similarity between voluntary and startReact movement traces. It was previously hypothesized that the inappropriate flexor activity results from an unsuppressed classic startle reflex - the adoption of a crouched stance that is dominated by flexor activity in the upper limb (Honeycutt and Perreault, 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous reports at the elbow showed inappropriate flexor activity that lead to deviations away from stroke subject's intended target (Honeycutt and Perreault, 2012, Honeycutt and Perreault, 2013); however we did not find evidence of this in the hand indicated by a strong similarity between voluntary and startReact movement traces. It was previously hypothesized that the inappropriate flexor activity results from an unsuppressed classic startle reflex - the adoption of a crouched stance that is dominated by flexor activity in the upper limb (Honeycutt and Perreault, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…During startReact trials, the GO signal was replaced by a startling, high-intensity acoustic stimulus (128 dB) emitted from a loud speaker located behind the subject's head. StartReact protocols are similar to those in previous reports (Honeycutt, Kharouta, 2013, Honeycutt and Perreault, 2012, Honeycutt and Perreault, 2013). Command signals for WARNING, GO, and the startling acoustic stimulus were generated in MatLab and their analog signals recorded to ensure they were delivered at the appropriate latency.…”
Section: Methodssupporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies have shown that startReact is robust across multiple individual joints, but startReact has also been shown to be more variable in kinematics such as mean peak displacement and peak angular velocity (Carlsen et al 2004a). Many previous studies restricted all joints not specifically related to the task (Carlsen et al 2004a; Maslovat et al 2011; Honeycutt and Perreault 2012, 2013) raising the question of whether startReact would be accurate during unrestricted multi-joint movements that more closely resemble functional reaching movements in everyday environments. Further, previous work to date (including our own) has primarily utilized statistical models that test for differences, not similarity, leaving in doubt if startReact movements were truly similar or simply “not different.” Our results show that multi-joint startReact movements are indeed equivalent to voluntarily-initiated movement demonstrating that startReact evokes a sophisticated motor plan with tuned direction, force, and muscle activation patterns that can be involuntarily initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike some other authors [4, 12, 13], we included all SAS trials in our analyses, regardless of whether a startle reflex was observed in SCM. Some previous studies on upper limb movements have reported small differences in SAS-induced reaction times between SCM+ and SCM− trials and argued that a startle reflex appears to be conditional to the StartReact effect [6, 7, 14].…”
Section: Discussionmentioning
confidence: 99%